Pandangan Tokoh-Tokoh Muslim mengenai Sabar sebagai Metode Penyembuhan Penyakit Hati - Ipah Saripah (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to discuss the views of Muslim leaders as a method of healing liver disease. This research is included in the type of qualitative research by applying a descriptive-analytical method. The data sources of this research include primary data sources and secondary data sources. Primary sources for this research include literature on liver disease and patient. Sources of secondary data are literature data related to the topic of this research including from journal articles, books, and others. Meanwhile, data analysis was carried out through the stages of inventory, classification, and interpretation. The results and discussion in this study show that patience can be a method of healing liver disease. This study concluded that liver disease can change the image and will of the heart. The description of syubhat (vague things) makes it difficult to discern truth or error. As a result, people who are affected by heart disease in themselves will hate useful truths and even like falsehood which in the end will bring people to harm, therefore, this dirty liver or heart disease needs to be cleaned so that it avoids these qualities and bad thing.